P402Analysis of right atrium remodeling by cardiac magnetic resonance in patients with atrial fibrillation and its association with left atrium. (18th June 2020) - Gunturiz Beltran, C; Borras-Amoraga, R; Alarcon, F; Garre, P; Figueras, R; Caixal, G; Cozzari, J; Trotta, O; Tolosana, J M; Arbelo, E; Roca, I; Brugada, J; et al.
Abstract: Funding Acknowledgements: none Background: Atrial fibrillation (AF) causes changes in atrial anatomy and this remodeling leads to the arrhythmogenic substrate. Most studies with cardiac magnetic resonance-late gadolinium enhancement (CMR-LGE) have focused on the left atrium (LA); The role of the right atrium (RA) in AF is unknown. Purpose: To evaluate RA remodeling parameters and its comparison with LA in patients with AF. Methods: Observational study. We included 109 patients: 9 healthy volunteers, 55 paroxysmal AF, 45 persistent AF. All of them had a CMR-RTG 3.0 T. Image post-processed with segmentation of both atria. Comparison of mean parameters of RA and LA (T test), correlation between them (R Pearson). Multivariate analysis (Cox regression) to study predictive factors. Results: AF patients had a mean age of 58.5 ± 10.5 years, 70(70%) were men, without structural heart disease 80(80%), and associated atrial flutter 11(11%). The RA parameters were compared by subgroups. We found differences in (healthy/paroxAF/persistAF): area(cm2) 94.0 ± 15.9 /125.3 ± 20.8/ 152.8 ± 24.4 (p <0.0001); volume (ml) 76.7 ± 19.6/ 107.0 ± 25.6/ 150.9 ± 37.6 (p <0.0001); and total fibrosis (%) 3.7 ± 4.3/ 16.5 ± 14.1/ 19.4 ± 15.9 (p 0.014). RA was higher than LA in all subgroups. There was more fibrosis in RA in paroxysmal/persistent AF. Both types of AF had at least a moderate correlation for area, volume and fibrosis (table). Finally, RA sphericity was the only predictor factor of AF recurrence after ablation among RA remodeling parameters (HR 1.1 95%CI [1.0 -1.3], p = 0.049). Conclusions: Area, volume and fibrosis progressively increased from healthy to paroxysmal AF, and then to persistent AF. RA was higher than LA and it also had more fibrosis in patients with AF. The size and fibrosis between both atria had at least moderate correlation. The RA sphericity was a predictor of post-ablation AF recurrences.